A Comparative Study of Health System Management Models in Combating Chronic Diseases - Moosa Al Riyami (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This Paper sheds shed light on the requirements for patients with chronic disease as well as describe the changes necessary for current health systems to meet these needs and tackle the chronic disease burden. The Author discusses list and explain some of the models used currently to manage chronic disease, such as the Chronic Care Model (CCM), Innovative Care for Chronic Conditions (ICCC) framework, and Kaiser Pyramid. By describing these requirements, the paper formulate the business model of the traditional health system. Finally, I will connect each section with the new business model proposed in this chapter to assess its efforts towards changing the health system in order to tackle the chronic disease burden.